Employee Participation in Profit and Ownership – Impact on Work Efficiency - Kozłowski, Maciej (Comparative Economic Research. Central and Eastern Europe, 2013)
In the vast theoretical literature, a number of arguments have been put forward in favor of employee financial participation schemes. Although traditionally the main arguments were spurred by objectives such as greater equality in the distribution of income and wealth and improving relations between workers and capitalist owners, today employee financial participation schemes are considered as part of industrial relations based on innovative managerial strategies and more flexible remuneration policies, which should ultimately result in increased enterprise efficiency. Because share ownership and profit sharing schemes are undoubtedly the most popular schemes, emphasis has been put on showing the multidimensional relationships between employee financial ownership and economic results, as well as on proving that the relationship between employee ownership and productivity involves an inherently complex interaction. The purpose of this paper is to present selected views and attitudes toward the relationship between employee participation and company results. The theoretical view and empirical research both indicate that after many years of conducting empirical research on the benefits resulting from the implementation of financial participation plans, the information provided, almost entirely by reports, is not yet sufficient to make any unequivocal conclusions concerning the influence on the results (productivity) achieved by companies. Obtaining such a consensus is additionally hindered because of the lack of clear-cut data concerning the extent to which implemented participation schemes contribute to changes in financial results. In conclusion, both the previous theory as well as the research conducted so far do not convincingly explain the relationship between financial participation schemes and the results achieved owing to their implementation, which demonstrates that there is a need to conduct further research in this field. In this case any empirical approach should concentrate on qualitative, not quantitative research, the latter of which, although broad based, does not identify the above mentioned relationships precisely enough. Another conclusion that can be drawn is the necessity to conduct further research based on larger samples of companies, taking into account the specificity of their business and working environment. It seems that some other aspects should be also taken into consideration, such as the type of the financial participation scheme introduced, because this decision may also have an influence on future results. Research should begin a long time prior to the introduction of a scheme in the company, which would allow for making future comparisons and evaluations of the influence of a given scheme on productivity.